Sociopolitical categories evaluated in nutrition programs and policies in Latin America (2017)
ABSTRACT: The evaluation of nutrition programs and policies has traditionally focused on analysing the impact and biological outcomes of their actions. Objective: To examine whether evaluations of nutrition programs include the following sociopolitical categories: (a) the right to food; (b) citizenship building; (c) civil participation in public policies; (d) women’s empowerment; and (e) territoriality in policy planning. Methodology: A comprehensive literature review of articles and documents that evaluate food and nutrition programs carried out in different Latin American countries and published during 2005-2013. Results: It was found that the evaluations carried out generally do not use these categories. In the cases where they are used, the conceptual development applied to the evaluation process is still incipient. Discussion: This study analyzed the sociopolitical categories of: the right to food; citizenship building; civil participation in public policies; women’s empowerment; and territoriality in policy planning, and found that although these categories are not prioritised when nutritional programs in Latin America are assessed, in most cases they form the basis of these programs. Conclusion: Social protection nutrition programs demand new objectives and actions. It is necessary to apply evaluation criteria that account for these new underpinnings in order to establish consistency between government institutions’ discourse, and the reality of their efforts.